KUNJUNGAN PASTORAL : STRATEGI PENDAMPING HOLISTIK KEPADA JEMAAT MELLUI PROGRAM INTEGRASI PKM MAHASISWA - Gita Yuventia Rauf (PT. Giat Konseling Nusantara, 2026)
This study analyzes a holistic support strategy integrated through a Student Community Service (PKM) program at the GMIST Efrata Buha Congregation in Tagulandang. The introduction highlights the shifting role of the church into a healing community for congregants in island regions who face limited access to mental health services and social pressures. This research uses a descriptive qualitative method, with data gathered through participant observation, in-depth interviews, and documentation during a four-day program. The results show that a strategy combining educational seminars for church elders, spiritual revival services (KPI), and home visits effectively increased the openness of the congregants. Home visits proved to be a vital tool in detecting psychosomatic issues, where residents’ physical complaints were found to be rooted in suppressed emotional burdens. Furthermore, the collaboration between students and local church leaders successfully built trust and maintained professional confidentiality. In conclusion, a holistic and personal pastoral support model within the home environment is highly effective in providing emotional healing while strengthening the faith of the congregation. This success emphasizes the importance of integrity, clinical competence, and empathy in all forms of pastoral service in the field.